EXPLORING INTERACTIVITY, TRENDS, AND ELECTRONIC WORD-OF-MOUTH (EWOM) OF SOCIAL MEDIA MARKETING THROUGH TIKTOK PLATFORM TO ENHANCE ONLINE CONSUMER ENGAGEMENT: A STUDY CASE OF VITABUMIN CHILDREN’S MULTIVITAMIN - Egi Pranajaya; Nila Armelia Windasari (Derivatif : Jurnal Manajemen, 2025)
This study aims to explore the Social Media Marketing Activities (SMMA) strategy used by the Vitabumin Children's Multivitamin in increasing online consumer engagement through the TikTok platform. A qualitative approach with a case study method and source triangulation technique was used to obtain data from content analysis, interviews with the marketing team, and interviews with TikTok users. The results show that the three main elements of SMMA-interactivity, trends, and electronic word-of-mouth (eWOM)-have a significant influence on the level of consumer engagement. However, the effectiveness of these strategies is constrained by limited human resources, technical restrictions from the platform, and not optimal utilization of TikTok's interactive features. Strategies that proved effective include utilizing educational content with an emotional approach (POV Gen Z Mom), collaboration with Key Opinion Leaders (KOL) and Key Opinion Customers (KOC), and building digital communities to create authentic eWOM. This research provides practical implications for brands in designing adaptive, relevant, and community-based content strategies to increase awareness and engagement in a sustainable manner. Future research could compare the effectiveness of SMMA elements (interactivity, trendiness, and eWOM) across TikTok, Instagram Reels, and YouTube Shorts in enhancing online consumer engagement and brand trust for children’s health products.Keywords: TikTok, social media marketing activities, online consumer engagement, eWOM, interactivity, trends, kids multivitamin